1984
DOI: 10.1080/07391102.1984.10507506
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Anti-poly[d(G-br5C)] IgG with Synthetic, Viral and Cellular Z DNAs

Abstract: Enzymatically synthesized poly[d(G-br5C)] was used to prepare specific polyclonal and monoclonal anti-Z DNA IgGs. The binding specificities of these antibodies were characterized using left-handed polynucleotides with the sequences d(G-x5C)n and d(A-x5C)n.d(G-T)n (mean = aza, methyl, bromo, or iodo). Polyclonal anti-poly[d(G-br5C)] IgG binds the convex surface of the Z helix as evidenced by the strong requirement for a methyl or halogen group at the C5 position of cytosine. Little or no anti-poly[d(G-br5C)] Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…Furthermore, dimers, trimers, and other multimers were observed. Previously, we have shown that these multimers are formed by the binding of bivalent anti-Z-DNA IgGs to Z-DNA tracts on individual DNA molecules (3,4,7,8). In contrast, there was no reactivity of form I M13 or pBR322 at their extracted negative superhelical densities with C-6, D-4, or normal rabbit IgGs (Fig.…”
Section: Methodsmentioning
confidence: 84%
See 4 more Smart Citations
“…Furthermore, dimers, trimers, and other multimers were observed. Previously, we have shown that these multimers are formed by the binding of bivalent anti-Z-DNA IgGs to Z-DNA tracts on individual DNA molecules (3,4,7,8). In contrast, there was no reactivity of form I M13 or pBR322 at their extracted negative superhelical densities with C-6, D-4, or normal rabbit IgGs (Fig.…”
Section: Methodsmentioning
confidence: 84%
“…Direct RIA or competition assays with unlabeled polymers or drugs were as described (3)(4)(5) Cytological Preparations, Immunofluorescent Staining, and Photomicroscopy. Crithidia luciliae and Crithidia fasciculata were propagated in culture medium containing 37 mg of brain-heart infusion per ml (Difco) and 25 ,ug of hemin per ml.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations